Mechanical, Thermal Properties and Morphological Behaviour of Grafted Polyolefin Nanocomposites - Santhoskumar*, A.U.; Lakshmi, S.U.; Palanivelu, K. (Asian Journal of Chemistry, 2013)
Ultra high molecular weight polyethylene is chosen as the base material for this project. With the modification of ultra high molecular weight polyethylene by blending with ethyl vinyl acetate in the ratio of 90:10, 7:30 and 50:50 for imparting polar characteristics to the polyolefin. From the SEM images it was found that the two polymers were not completely miscible. Hence, maleic anhydride was used as the grafting material or compatibilizer. 5 % of Maleic anhydride was found to be optimum which was added along with the above three ratios. This resulted in considerable improvement in degradation temperature, mechanical properties such as tensile strength, impact strength and tensile modulus. The nanoclay as closite Na+ was added. The optimum percentage of the nanoclay was found to be 3 %. The addition of nanoclay showed improvement in the properties.